Social Machines: Looking at the bright side of Robots - Oliveira, R.; Arriaga, P.; Paiva, A. (4º Congresso da Ordem dos Psicólogos Portugueses, 2018)
Social robots are currently being deployed to assist and to collaborate with people on many settings. However, despite this increasingly larger presence, negative social stigmas, such as the fear of being replaced or mistreated by a robot are still a common place for most people. Nonetheless, research on human-robot interaction has yielded a significant list of beneficial effects stemming from the interaction with robots. In this work we will present an overview of Human-Robot Interaction studies in the educational, assistive care and entertainment settings in order to unveil how these social machines can positively influence these activities. More specifically, our goal will be to critically analyze (1) in what ways robots have been and are currently being used in these settings, (2) how form follows function and how the way these robots are being developed and used is based on research about the human behavior, and finally (3) what are the positive outcomes, in each of the areas mentioned above, that are brought about from interacting with robots. Societal and social implications of the increasingly integration of social machines will be further discussed in light of the findings from psychology and Human-to-Human interaction.